Double-layer closure techniques after bone surgery of medication-related osteonecrosis of the jaw: a single center cohort study - Ristow, Oliver; Rückschloß, Thomas; Bodem, Jens; Berger, Moritz; Kargus, Steffen; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2018)
Introduction - Mucosal wound closure plays a key role after surgery of manifested medication-related osteonecrosis of the jaw (MRONJ). Additional soft tissue layers promise better vascularization and mechanical stability. The objectives of this study were to examine success rates of double-layer closure techniques in MRONJ patients, namely the mylohyoideus muscle flap (MMF) for the lower jaw and the pedicled buccal fat flap (BFF) for the upper jaw. - Materials and methods - We designed and implemented a restrospective cohort study and enrolled a sample of patients diagnosed with MRONJ that were treated between 2015 and 2017 with either the MMF or the BFF after removal of the necrotic bone areal. Success was assessed as the maintenance of full mucosal coverage without signs of residual infection at (T0) four weeks (T1), four months (T2), and eight months (T3) after operation. The occurrence of side effects was evaluated. - Results - A total of 87 (MMF n = 57; BFF n = 30) patients with 104 MRONJ (MMF 68 = ; BFF n = 36) lesions were included. At the time of the last follow-up, 88.0% (44 of 50) of patients in the MMF group and 93.1% (27 of 29) of patients in the BFF group showed mucosal integrity. No serious side effects were reported. Overall treatment of earlier lesions (stage I and II) showed a better outcome than more severe necrosis (stage III). - Conclusion - Double-layer closure techniques after surgery in MRONJ patients provide a mechanically stable, well-vascularized covering of the bone defect and should be considered as an option in the standard protocol for all degrees of severity of the disease.
Gesehen am 14.04.2020